Sosialisasi Keselamatan Di Laut Bagi Masyarakat Pulau Balang Lompo - Hasdinar Umar; Daeng Parokka; Achmad Yasir Baeda; Chairul Paotonan; Sabaruddin Rahmanr (Faculty of Engineering UNHAS, 2021)
Public sea transportation is a vital means for people living on small islands, such as Balang Lompo. This facility functions as sea transportation tools, for both goods and passengers. Lack of operators and users understanding of these facilities, is one of the factors causing accidents at sea. The aim of this activity is to increase Balang Lompo community understanding, due to the importance of the safety at sea when they are using a ship as a public transportation facility. This activity was carried out using a questionnaire survey to 57 respondent which also residents of Balang Lompo Island; with an atractive activity also carried out at the distribution of safety equipment instructions to respondent due to their activity as users of public transportation facility. The successfulness of the program then evaluated by using a questionnaire distributed before and after the socialization of on board safety. After the socialization, there was an increase of 3.6 to 4.1 points in the average value of the public understanding of the safety aspects before the socialization; besides that the respondents generally understood well that if an accident at sea occurs, they can use not only the door but also sidescuttles that have been made wider, to exit the ship calmly and in safely manner.